Reposisi Identitas Sosial Perempuan Saudi Pasca Terbitnya Visi Saudi 2030 - M Zulifan Zulifan (Hasanuddin University, 2022)
Abstract This study examines the social and cultural changes of Saudi Arabian society and their impact on women after the launch of Saudi Vision 2030 by Muhammad Bin Salman (MBS). Saudi Arabian women were previously positioned in the domestic sphere with strict restrictions not to participate in the public sphere. However, as a consequence of the economic liberalization program, MBS offers fresh air to change gender relations in Saudi Arabian society by opening public spaces for women to contribute. This qualitative research utilizes the information obtained through social media in Saudi Arabia to be critically studied by placing it as a discourse (discourse). Foucault's theory of Critical Discourse Analysis (1980) is used as an analytical knife to examine social changes in women in Saudi Arabia driven by royal actors who have so far limited women's position. This study found a change in the social and political roles of women in the Kingdom of Saudi Arabia after the Saudi Vision 2030 was launched. The change is a consequence of the openness designed power (MBS). The kingdom no longer places civil society as an object, but as a subject of development. Keywords: Saudi Arabia; Saudi Vision 2030; Women; Social Identity.